Towards a consensus on the clinical applications and interpretations of the nailfold capillaroscopy standards in clinical practice: An initiative by the Egyptian Society of Microcirculation - Yasser El Miedany; Sherif Ismail; Mary wadie fawzy; Ulf Müller-Ladner; Roberto Giacomelli; Vasiliki Liakouli; W Hermann; Nihal Fathy; Maha El Gaafary; Nermin A Fouad; et al. (Archives of Rheumatology, 2023)
Objectives: Based on the mainstream adoption of nailfold capillaroscopy as an investigative tool for rheumatologists, this work was carried out by a panel of experts in the field of capillaroscopy and microcirculation to issue a consensus view on capillaroscopic image acquisition and analysis standardization. Patients and methods: After the key clinical questions were identified by the core team, a systematic review of the published research was carried out focusing on variable capillaroscopic techniques, definitions, and characteristics, including capillary density (number of capillaries), capillary morphology (shape of each capillary), capillary dimensions (width of apical, arterial, and venous limb of the capillary), and the presence of hemorrhages. The expert panel attained a consensus and developed recommendations for the standardization of capillaroscopy in clinical practice. These included recommendations for normality and abnormality and the different capillaroscopic patterns. It also involved recommendations for scoring systems, reliability, and reporting. Results: A panel of 11 experts participated in the two rounds with a response rate of 100%. A total of nine recommendations were obtained. The agreement with the recommendations (a score of 7-9) ranged from 81.8 to 90.9%. A consensus (i.e., ≥75% of respondents strongly agreed or agreed) was reached on all the clinical standards. Conclusion: This work highlighted the main NFC indications, the technical equipment that should be used, how to carry out the procedure, standardization of the terminology of the parameters, and the interpretation of NFC findings. An evidence-based consensus incorporating the advice and experience of a diverse international expert panel was reached.